Chemical and environmental assessment of the bottom sediments in the Irtysh River (Tyumen Region, Russian Federation) - Zemtsova E. S.; Alimova G. S.; Tokareva A. Yu. (Vestnik MGTU, 2019)
The total concentration of Al, Co, Fe, Mn, Pb, Cu, Zn, Sr, As, Cr, Ni has been determined in the test portions of the bottom sediments (sand, loamy sand, sandy loam, silt and clay loam) in the lower reach of the Irtysh River. Atomic emission spectroscopy has been used. The established concentrations do not exceed background indicators, except for Pb and As. Their maximum values are 138 and 7.2 mg/kg, respectively. Gross concentrations of metals and metalloids are in close correlation with the content of various particle size fractions in the river sediments. Emission status of the bottom sediments has been analyzed with account of particle-size classification. As a result, multiple regression equations have been obtained. The equations reflect mathematical relationship between concentration of different elements and two regressors – the proportion of clay and silt particles in the bottom sediments of the Irtysh River. Based on these equations and determining the percentage of various particle-size fractions in soils, it is possible to predict the most probable amount of the metal concentration in the test portion. The content of oil products in bottom sediments of the river has been determined by IR spectrometry. The concentration of oil products in 24 % of test portions does not exceed the maximum permissible limit equal to 20 mg/kg. The concentration of oil products varies from 21 to 73 mg/kg in the remaining test portions of the bottom sediments. The statistically significant correlations of the gross concentrations of elements with iron, manganese, organic substance and oil products in the bottom sediments of the lower reach of the Irtysh River have been revealed. The weak statistically significant pH correlations with indicators of the particle-size classification of bottom sediments have been determined